THE POTENTIAL OF CORN SPROUT FLOUR AS AN ALTERNATIVE AS BASIC MATERIALS OF WEANING FOOD - Humaira Anggie Nauli; Albiner Siagian; Posman Sibuea (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Weaning food given to babies older than 6 months. Weaning food intake should come from different types of materials adapted to the manufacture of the local food supply. Corn (Zea mays) is one of Indonesian eminent local food but is not used as well as possible as weaning food. The germination aims to increase corn’s nutritions like protein and mineral. This is a descriptive explorational research. The corn sprout flour was made in one way then its nutritional value determinated. The determinations are analysis of protein, fat, carbohidrate, water, Fe, and zinc. The Corn sprout flour’s nutrition value is compared to instant weaning food regulation of Indonesia and also local weaning food guidance. There is also determination of corn sprout flour’s water absorption to understand it as nutrient dense weaning food. Result showed that corn sprout flour has 4,5 g protein; 4,04 g fat, 60,10 g carbohidrate, 11,44 g water, 1,55 mg Fe, 2,94 mg zinc, and 19,92 g ash every 100 g. It has a low water absorption which it can be one of nutrient dense weaning food. In accordance with 7-11 months baby and 1-3 years young children, corn sprout flour is marvelous zinc source. While the protein, fat, carbohidrate, water, and ferrum are not balance enough if used as single component of weaning food. Therefore, it is recommended to combine corn sprout flour with another food to appropriate the weaning food standart. It is recommended to review another nutrient of corn sprout flour especially vitamin and mineral and also to make weaning food formula based corn sprout flour. Keywords : corn sprout flour, weaning food, local food.